2019
DOI: 10.1093/mind/fzz017
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge From Vice: Deeply Social Epistemology

Abstract: In the past two decades, epistemologists have significantly expanded the focus of their field. To the traditional question that has dominated the debate — under what conditions does belief amount to knowledge? — they have added questions about testimony, epistemic virtues and vices, epistemic trust, and more. This broadening of the range of epistemic concern has coincided with an expansion in conceptions of epistemic agency beyond the individualism characteristic of most earlier epistemology. We believe that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 75 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…If each of us can predict how the others will behave, we can more efficiently play our part in joint actions, without interfering with one another or introducing redundancies. By communicating which aspects of our behavior are intentional, we indicate what should be copied and what may safely be ignored, thereby facilitating the transmission of cultural knowledge (Levy & Alfano, 2019). Perhaps most importantly, making beliefs explicit allows them to be displayed to others.…”
Section: Resultsmentioning
confidence: 99%
“…If each of us can predict how the others will behave, we can more efficiently play our part in joint actions, without interfering with one another or introducing redundancies. By communicating which aspects of our behavior are intentional, we indicate what should be copied and what may safely be ignored, thereby facilitating the transmission of cultural knowledge (Levy & Alfano, 2019). Perhaps most importantly, making beliefs explicit allows them to be displayed to others.…”
Section: Resultsmentioning
confidence: 99%
“…Similar links between ecology, social norms, and navigational ability have been identified in other studies among non-WEIRD children. For example, among the Mbendjele BaYaka in the Republic of Congo, children spend considerable time in work and play away from home beginning at an early age (Lew- Levy et al 2020), and on a similar pointing task their navigational error was found to be as low as 7° (Jang et al 2019). Likewise, in a seminal study among Alaskan school children (Kleinfeld 1971), children of native Alaskan descent, primarily Iñupiaq, demonstrated far greater visual spatial memory than their European-descent peers.…”
Section: Spatial Navigationmentioning
confidence: 99%
“…Smart describes the phenomenon as an instance of collective epistemic virtue arising out of individual epistemic vice (Smart 2018b). Other authors have also described in recent years the way individual epistemic vices contributing to emergent epistemic goods (Levy and Alfano 2019;Morton 2012). In some cases, knowledge arising out of bad epistemic character can be a lucky fluke.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent work in epistemology has expanded the notion of epistemic virtue in such a way that Mandevillian intelligence is more easily accounted for. Various authors have proposed theories about shared-belief formation, collective epistemic virtues and the social extension of epistemic virtues (Gilbert 1987;Fricker 2010;Alfano and Skorburg 2016.;Levy and Alfano 2019;Palermos 2016; Pritchard 2018) Such developments allow epistemic virtue theories to account for emergent epistemic goods, even when they arise out of vice. However, moral virtue theories have not seen this kind of developments.…”
Section: Introductionmentioning
confidence: 99%